Formulation development, in-vitro and ex-vivo evaluation of dry adsorbed solid lipid nanoparticles: an approach of overcoming olanzapine drawbacks - Hirlekar Rajashree; Momin Alfiha; Bhairy Srinivas (Sciendo, 2024)
The present study was aimed at preparing stable dry adsorbed nanoparticles (DANs) of olanzapine (OLZ) loaded solid lipid nanoparticles (SLNs) for sustained release.